Partial purification and identification of three antioxidant peptides with hepatoprotective effects from blue mussel (Mytilus edulis) hydrolysate by peptic hydrolysis. (January 2016) - Park, Soo Yeon; Kim, Young-Sang; Ahn, Chang-Bum; Je, Jae-Young
Highlights: Antioxidant peptides were produced from Mytilus edulis protein by enzymatic hydrolysis. PIIVYWK (1004.57 Da, P1), TTANIEDRR (1074.54 Da, P2), and FSVVPSPK (860.09 Da, P3) were identified. P1 and P3 exhibited more potent ORAC values than P2 antioxidant peptide. P1 and P3 protected hepatocytes against H2 O2 -induced hepatic damage through the upregulation of HO-1. Abstract: Antioxidant peptides were purified from Mytilus edulis hydrolysates by peptic hydrolysis using consecutive chromatographic techniques with SP-Sephadex C-25 cation-exchanger and reverse-phase-high performance liquid chromatography. Three antioxidant peptides including PIIVYWK (1004.57 Da, P1), TTANIEDRR (1074.54 Da, P2), and FSVVPSPK (860.09 Da, P3) were identified by LC-MS/MS. P1, P2, and P3 exhibited strong DPPH radical scavenging and ORAC activity. P1 and P3 were found to be more potent antioxidant peptides than P2. Thus, hepatoprotective activities of P1 and P3 were evaluated against H2 O2 -induced hepatic damage in cultured hepatocytes. P1 and P3 significantly ( p  <   0.05) increased cell viabilities in H2 O2 -induced hepatotoxicity. Furthermore, P1 and P3 upregulated heme oxygenase-1 (HO-1) under normal and oxidative stress conditions in cultured hepatocytes. However, hepatoprotective abilities of P1 and P3 were abolished in the presence of ZnPP, HO-1 inhibitor. Thus P1 and P3 exhibited hepatoprotective effects through activation of HO-1 expression.